Partial Insurance and Investments in Children - Pedro Carneiro; Rita Ginja (Institute for the Study of Labor (IZA), 2015)
This paper studies the impact of permanent and transitory shocks to income on parental investments in children. We use panel data on family income, and an index of investments in children in time and goods, from the Children of the National Longitudinal Survey of Youth. Consistent with the literature focusing on non-durable expenditure, we find that there is only partial insurance of parental investments against permanent income shocks, but the magnitude of the estimated responses is small. We cannot reject the hypothesis full insurance against temporary shocks. Another interpretation of our findings is that there is very little insurance available, but the fact that skill is a non-separable function of parental investments over time results in small reactions of these investments to income shocks, especially at later ages.
Keywords: D12; D91; I30; J1; 330; insurance; human capital; consumption